Upaya KUA Kecamatan Jombang Dalam Mencegah Pernikahan Dini Perspektif Maslahah Mursalah Tahun 2022-2023 - Ayatulloh Masyhudi; Muhammad Muhammad (JURNAL ILMIAH NUSANTARA, 2025)
Marriage is a powerful vow, or misaqan galizan, and doing it to follow Allah's will is worth worship. According to Law Number 16 of 2019, which later revised Law Number 1 of 1974, the minimum age for marriage is 19 years. Despite this, society still makes exceptions to this rule, which is where the term "early marriage" comes from. In Indonesia, early marriage is not a strange thing, as happened in Jombang District, Jombang Regency. Cases of irregularities committed by the local community will undergo a special review by the authorized agency, namely the Jombang Regency KUA, in order to develop preventive measures. As a form of concern for society, this research looks at the steps taken by the Jombang Regency KUA to avoid early marriage. This research is empirical normative research that uses primary and secondary data. Interviews with the Jombang Regency KUA provided primary data which was then examined from the perspective of maslahah murlah. Classical and contemporary books, as well as scientific books and journals, constitute secondary data. Research findings show that a number of factors, including low spirituality, poverty, education, socio-culture, social media, and factors causing out-of-wedlock pregnancies, contribute to the high rate of early marriage in Jombang Regency. Then, the socialization of the Jombang Regency KUA to the community in an effort to prevent early marriage shows the problem of maintaining the five basic aspects of life, because a lack of it will have an impact on fulfilling the requirements for maintaining hifz ad-din, hifz an-nafs, hifz a-nasl, hifz al-' aql, and hifz al-mal.